IMPLEMENTASI PROBLEM SOLVING BERORIENTASI HOTS PADA PEMBELAJARAN IPS SD - Maiyona Ovartadara; Yeni Erita; Ummul Khaira (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
Seeing the many problems experienced by students in solving HOTS-based problems, this research was conducted to see the extent to which students' thinking skills at the elementary school level were in solving problems. Student learning activities are not focused on finding a concept but rather on memorizing it, and book-based learning does not foster critical thinking skills. Therefore we need a Problem Solving learning model as a learning model that can help. students develop their Higher-Order Thinking Skills. The purpose of this research is to ascertain how social studies teaching in elementary schools incorporates HOTS-oriented problem solving. The research method used is qualitative library research without going into the field, library research is an activity to collect research data that is appropriate or relevant to a topic or problem as a research object. This research can be used as a reference for elementary school teachers to implement learning in their classes. As a result, teachers can use it to overcome learning challenges.